2014
DOI: 10.1016/j.mex.2014.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of the formation of biofilm in industrial pipes using enzyme cleaning technique

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Once formed, biofilms can be extremely difficult to remove, leading to contamination of processing equipment (Kumar and Anand, 1998; Tan et al, 2014), food spoilage and consequent economic losses (Brooks and Flint, 2008; Houdt and Michiels, 2010). Numerous studies have described the use of novel approaches to control biofilms; these have included the use of biocides (Wood et al, 1996), application of electrical currents (Poortinga et al, 2001), temperature step changes during growth regions (Knight et al, 2004), enzymes (Liu et al, 2014) and for biofilms on or within a food matrix, the use of novel food additives (Furukawa et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Once formed, biofilms can be extremely difficult to remove, leading to contamination of processing equipment (Kumar and Anand, 1998; Tan et al, 2014), food spoilage and consequent economic losses (Brooks and Flint, 2008; Houdt and Michiels, 2010). Numerous studies have described the use of novel approaches to control biofilms; these have included the use of biocides (Wood et al, 1996), application of electrical currents (Poortinga et al, 2001), temperature step changes during growth regions (Knight et al, 2004), enzymes (Liu et al, 2014) and for biofilms on or within a food matrix, the use of novel food additives (Furukawa et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Disruptive enzymes, such as proteases, glycosidases, amylases, cellulases, or DNAses, are considered a green alternative to chemical treatments often used in the fight against biofilms' formation in food-related environments [2]. Such enzymes do not have toxic effects and are used both alone and as part of the industrial detergents' composition to improve their cleaning efficacy [64][65][66].…”
Section: Disruptive Enzymes For Fighting Against Biofilmsmentioning
confidence: 99%
“…Traditional cleaning agents are also known to be ineffective and do not clean or sterilize microbes located in the inner layers of the biofilm [8]. A recent study has identified a class of fluids known as enzyme fluids [9][10] to be effective for removing biofilms in pipes. These enzyme fluids are specifically being highlighted here, as these fluids are organic and thus will be safe for human use.…”
Section: Introductionmentioning
confidence: 99%